Pengaruh Motivasi Belajar dan Efikasi Diri terhadap Hasil Belajar Kimia Peserta Didik Kelas XI MIPA MAN 1 Sinjai - Bachtiar, Hilmi Magfirah; Anwar, Muhammad; Salempa, Pince (Program Pasca Sarjana UNM, 2023)
This research is an ex-post facto research that is causal in nature with the aim of knowing the effect of learning motivation and self-efficacy on the chemistry learning outcomes of class XI MIPA MAN 1 Sinjai on acids and bases. The research sample consisted of 30 students in class XI MIPA MAN 1 Sinjai for the 2022/2023 academic year who were selected using cluster random sampling. The independent variable in this study is learning motivation and self-efficacy while the dependent variable is the results of students' chemistry learning on acids and bases. Data collection techniques used questionnaires on learning motivation, self-efficacy questionnaires, and chemistry learning outcomes tests. The results of the descriptive statistical analysis showed that the students' motivation to study chemistry in class XI MIPA MAN 1 Sinjai was categorized as high, while self-regulation and students' chemistry learning outcomes were categorized as low. The results of inferential statistical analysis show: (1) learning motivation influences the chemistry learning outcomes of students in class XI MIPA MAN 1 Sinjai, (2) self-efficacy influences learning outcomes in chemistry class XI MIPA MAN 1 Sinjai (3) learning motivation and efficacy collectively influence the chemistry learning outcomes of students in class XI MIPA MAN 1 Sinjai at a confidence level of 95%.